THE TEACHING OF LANGUAGE - R., Suhartina (Universitas Hasanuddin, 2014)
In general, language teaching shifted from old method to modern one. The old method tended toplace more emphasis on the mastery of the rules of language or grammar rather than to thefunction of language as the primary means of communication for mankind. The implications ofthe method and / or the old approach was the birth of a second language learner or a foreignlanguage that is very capable in using the rules of the language but lacking even incompetent interms of communicating using the language. This reality motivated language teaching experts toswitch to a more functional approach thus was born the so-called communicative approach, theapproach in language teaching that requires students to use the language to the maximum duringthe learning process, although the rules of the language tend to 'negligible'. Real form of thecommunicative approach is the interaction established during the learning process by using thelanguage being studied. The interaction was not only between teachers and students (two waycommunication) but also between teachers and students and among students (multi-directional).Only the implementation of this approach is not without drawbacks, namely the birth of languagelearners who are able to communicate verbally very eloquent invitation but is hampered whendealing with tasks that require them created especially writing scholarly writings.Both of the above realities spawned the emergence approach called integrated approach, namelythe teaching of grammar rules of a language by using the language communicatively - interactiveduring the learning process. Although this approach is also not free from the possibility of thebirth of various constraints, such as the design of instructional materials that require specialexpertise and impeccable, setting and classroom management is also one of the considerationsthat can not be ruled out.Key words: Teaching English, communicative interactions.